Unaccompanied young migrants : identity, care and justice - Clayton, Sue; Gupta, Anna; Willis, Katie, 1968- (Bristol : Policy Press, 2019)
Exploring in depth the journeys migrant youth take through the UK legal and care systems, this text contributes new thinking, from a social justice perspective, on migration and human rights for policy, practice and future research.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 14, 2019).
Keywords: Immigrant children -- Great Britain -- Social conditions; Immigrant children -- Legal status, laws, etc. -- Great Britain; Immigrant children -- Government policy -- Great Britain; Social justice -- Great Britain; Great Britain -- Emigration and immigration -- Social aspects; Immigrant children -- North America; Immigrant children -- Scandinavia; Immigrant children -- Australia; Society; Society & culture: general